Microsoft Windows Identity Foundation cookbook : over 30 recipes to master claims-based identity and access control in .NET applications, using Windows Identity Foundation, Active Directory Federation Services, and Azure Acces Control Services /: over 30 recipes to master claims-based identity and access control in .NET applications, using Windows Identity Foundation, Active Directory Federation Services, and Azure Acces Control Services. (2012) - Unknown
No abstract available